2022
DOI: 10.15587/1729-4061.2022.267281
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the impact of information technology on the tourism supply chain performance in Vietnam

Abstract: In the context of the industrial revolution 4.0, information technology (IT) plays an essential role in the supply chain operation. Adopting IT helps companies stay competitive globally. Many researchers have highlighted the influence of IT on supply chain management and performance. It facilitates the linkages between components in the supply chain, minimizes operating costs, and enhances supply chain performance. Furthermore, IT helps increase the speed and quality of information exchange between partners in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In that regard, the study concluded that integration of information technology improves rms' ability and performance. Another comprehensive review by Nguyen and Hoang further concluded that the companies in the food industry have been adopting technology at an unprecedented rate to remain competitive 11 .…”
Section: The Impact Of Information Technology On Food Supply Chain Pe...mentioning
confidence: 99%
See 3 more Smart Citations
“…In that regard, the study concluded that integration of information technology improves rms' ability and performance. Another comprehensive review by Nguyen and Hoang further concluded that the companies in the food industry have been adopting technology at an unprecedented rate to remain competitive 11 .…”
Section: The Impact Of Information Technology On Food Supply Chain Pe...mentioning
confidence: 99%
“…It is also worth noting that these systems are crucial for responding to changes in consumer expectations and improving company loyalty 78,79 as well as reducing risks, ensuring safe consumption and lowering medical costs. Most of the companies have tried to harmonise traceability systems by implementing technology ranging from alphanumerical code, barcode and RFID to internet-based tracking and tracing products 11 .…”
Section: Food Traceability Impact and Food Supply Chain Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Businesses can combine with suppliers and even competitors in the chain to build a strong network to seek benefits for the whole system (Nguyen, 2012). This combination not only increases resources for enterprises, but also enhances creativity and strengthens the capacity and competitive position of enterprises in the network.…”
Section: Connection Capacitymentioning
confidence: 99%